PEMETAAN DAN PERBAIKAN TATA KELOLA KEUANGAN DESA MENGGUNAKAN PRAKARSA AKUNTABILITAS DAN TRANSPARANSI - Jopinus Saragih; Hendri Mayanta; Joel Fernando Sirait (Yayasan Nusantara Hasana Berdikari, 2024)
This Community Service (PkM) activity focuses on mapping and improving village financial management through accountability and transparency initiatives. Common issues include inconsistencies in planning, implementation, and administrative documents; delayed reporting; incomplete transaction records; unclear role definitions; and limited publication of information regarding the Village Budget (APBDes) and its implementation. The program is implemented through document compliance assessments, mapping of current processes, identification of risk gaps, development of improvement plans (SOPs, checklists, role matrices), strengthening of public transparency mechanisms (village information media, APBDes summary formats), and implementation support. Outputs include a village financial management process map, a package of SOPs and document checklists, a summary report template for the public, and an accountability indicator dashboard.